2017
DOI: 10.1371/journal.pone.0169308
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Attention Deficits in Adolescent Offspring Exposed to Maternal Type 1 Diabetes

Abstract: ObjectiveThe aim of this study was to examine the potential association between intrauterine exposure to maternal diabetes and attention deficits in the offspring.Research design and methodsAdolescent offspring of a prospectively followed cohort of women with type 1 diabetes (n = 269) and a control group from the background population (n = 293) participated in a follow-up assessment in 2012–2013. We used scores from Conners Continuous Performance Test II to assess attention and based on a principal component a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Unfortunately, publication bias was identified according to Egger’s test ( t =6.56, P =0.003) (Table 4), indicating that the estimated effect was probably overstated due to publication of positive results. Since only the Li et al’s11 study investigated the effect of maternal diabetes in Chinese, the remaining studies 10,12,13,19,20 that were conducted in Caucasian population demonstrated the risk in this race (RR: 1.37, 95% CI: 1.24–1.51). Subgroup analyses revealed that T1D increased the risk by 36% (RR: 1.36, 95% CI: 1.23–1.50) 12,13,19.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, publication bias was identified according to Egger’s test ( t =6.56, P =0.003) (Table 4), indicating that the estimated effect was probably overstated due to publication of positive results. Since only the Li et al’s11 study investigated the effect of maternal diabetes in Chinese, the remaining studies 10,12,13,19,20 that were conducted in Caucasian population demonstrated the risk in this race (RR: 1.37, 95% CI: 1.24–1.51). Subgroup analyses revealed that T1D increased the risk by 36% (RR: 1.36, 95% CI: 1.23–1.50) 12,13,19.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we were unable to replicate previous CPT-II factor structures (Bytoft et al, 2017;Vertinski et al, 2014) and the use of exploratory methods may have weakened associations among our neurocognitive predictors and outcomes.…”
Section: Limitationsmentioning
confidence: 69%
“…Evidence has been inconsistent regarding the validity of this factor structure. To our knowledge no study has successfully replicated a previously published Conners CPT factor structure despite multiple attempts (Bytoft et al, 2017;Vertinski et al, 2014).…”
Section: Neurocognitive Factor Constructionmentioning
confidence: 94%
See 2 more Smart Citations